ICT & Nursing Informatics Skills in Cyprus' Universities Undergraduate Nursing Curricula - Masouras, Panicos (My University, 2016)
Information and Communication Technology (ICT) skills for university nursing students is a well researched area; however there are different opinions as to whether ICT skills related courses should be taught in undergraduate nursing programmes. On one hand, authors suggest that the pervasive use of ICTs in secondary educations makes the teaching of ICT skills at university level unnecessary as students do have the required ICT skills to cope at university level. On the other hand, considering the digital divide and that underprivileged student may not have had equal access to use computers and the fact that students are mostly using computers for entertainment and socializing, it raises doubts as to whether new university students actually do have the ICT skills required to cope with their students. This paper will present the findings of an exploratory study that examined the content of nursing curricula of undergraduate programs in one public and three private universities in Cyprus in terms of the ICT skills and competencies included and taught in these programs. The study found that only the public university combines both ICT and nursing informatics skills in the curriculum and that private universities' content is limited to ICT skills only. The qualitative data was derived through unstructured interviews with representatives of the four universities and indicate that they do not consider ICT courses as an important component of their nursing curricula. The study recommends that university nursing curricula are upgraded to meet the ICT needs and competences that will be required for the effective implementation of the national health system in Cyprus in 2017.
Keywords: Competences; Curriculum; Cyprus; ICT; Informatics nursing; Skills